Weed seed bank size and composition in an arable crop mulched with pruning from three multipurpose trees in southwestern Nigeria - Kamara, A.Y.; Akobundu, I.O.; Chikoye, David; Jutzi, S.C. (1999)
Weed seed bank size and composition were analysed in 1995 and 1996 in maize fields mulched with pruning from Gliricidia sepium, Leucaena leucocephala, and Senna siamea in South Western Nigeria. Plots mulched with pruning from the three trees had a lower weed seed bank in the first year of cropping than unmulched plots. In the second year of cropping, the weed seed bank was higher than in the first year in the Gliricidia sepium, and Leucaena leucocephala mulch treatments by 41 and 65% respectively. Senna siamea had a lower seed bank at all times of sampling. Talinum triangulare, Sedges, Oldenlandia corymbosa and Ageratum conyzoides were the dominant species in the seed bank of all treatments. Mulched plots had a low seed bank of Oldenlandia corymbosa, and Ageratum conyzoides in all treatments but Talinum triangulare and sedges remained largely unaffected. Future weed control strategies with mulches in this area should therefore target the first named species. For weed management, Senna siamea mulch was the most effective in reducing seed bank